Peran Film â€œIntiq Rasmiyyatan Gontor TVâ€ Dalam Meningkatkan Motivasi Belajar Siswa Dalam Pembelajaran Bahasa Arab Di Kelas X MAN 3 Jombang - Imanuddin, Abdullah Syamil; Ghofur, Abdul; Muhdhor, Muhammad (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2024)
This article discusses the role of the film "Intiq Rasmiyyatan Gontor TV" in increasing students' learning motivation in learning Arabic. In the context of education, visual media such as films have great potential to attract attention and increase student engagement. This study examines how narrative and visual elements in the film can influence students' interest and enthusiasm for learning. The film "Intiq Rasmiyyatan" presents content that is relevant to the Arabic curriculum, combining an interesting story with cultural and linguistic values. With an interactive approach, this film is able to create a fun and not boring learning atmosphere. The author uses a qualitative method with interviews and observations of students and teachers in several schools that use this film in learning.The results of the study indicate that the use of this film can increase students' motivation in learning Arabic, as seen from the increase in active participation and enthusiasm of students during the learning process. Students who watched this film reported a more positive learning experience and felt more inspired to understand Arabic more deeply. Thus, this article concludes that the film "Intiq Rasmiyyatan Gontor TV" not only functions as a learning aid, but also as a means to motivate students in exploring Arabic and its accompanying culture. This research is expected to contribute to the development of more innovative and effective learning methods.